Performa Broiler yang Diberi Ransum Mengandung Daun Sengon (Albizzia falcataria) yang Direndam dengan Larutan Kapur Tohor (CaO) - Akmal Akmal; Mairizal Mairizal (Universitas Andalas, 2013)
This research aims at meauring the use of Sengon leaves soaked in kapur tohor and it’s effect on the performance of broiler. The Study used 100 broiler Hubber aged 3 days and 5 treatments ration which contain different Sengon. The design used in this study was completely randomized design (CRD) with 5 treatmen. Parameter measured were ration consumption, body weight gain, feed convertion and carcass. The result of this study shows that the use of sengon in the ration is effective significantly (P<0.05) on the ration consumtion, body weight gain,carcass and feed convertion. It could be concluded that Sengon can be used up to 7.5% in the ration of the broiler.